Deformations due to the processes of compaction, decompaction and phase transitions in the internal structures of the Earth - Kuliev, G. G. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2013)
Questions of dis tribution of medium depending on changes of deformation have been studied involving various elastic potentials using non-classical linearized approach within the limits of theory of small and large initial deformations and it has been shown that this dependence for various geological media is instable. Given processes contribute to e mergence of structures of formation deconsolidation zones. In p resence of different kinds of inclusions, free and contacted surfaces and cavities the p rocess of de formation occurs differently than assumed in experiments. Comparing the received theoretical results with results o f known experimental studies, it has been shown that the processes of loss of stability of elastic state of equilibrium on geometric shape change and on "internal" instability precedes the p rocesses of phase transitions of various mineral systems.